Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0175551
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of reactive red 241 by oxygen insensitive azoreductase purified from a novel strain Staphylococcus KU898286

Abstract: An oxygen insensitive azoreductase was purified from a novel bacterial strain (Staphylococcus sp. KU898286) that was isolated from an abandoned site of the textile waste discharge unit. The isolated enzyme had efficiently cleaved the azo-bonds through reductive transformation under aerobic conditions. Initial phenotypic characterization and final construction of phylogenetic tree on the basis of 16s rDNA demonstrated 99% resemblance of the isolate to Staphylococcus aureus. The purified azoreductase was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Further, a pathway was proposed for the breakdown of the Reactive Red 120 dye. The Reactive Red 120 dye structure was broken down by the cleavage of N=N azo bonds with the generation of unknown intermediate and 2‐aminobenzenesulfonic acid; it was converted into benzoquinone, which has been previously reported by Nisar et al (2017). The unknown intermediate was further reduced to sodium 4‐(6‐chloro‐4,5‐dihydro‐4‐imino‐1,3,5‐triazin‐2‐ylamino)‐5‐hydroxynaphthalene‐2,7‐disulfonate, which was reduced to 2‐(2‐amino‐2‐formylethyl)‐3‐hydroxybenzoic acid.…”
Section: Resultsmentioning
confidence: 65%
“…Further, a pathway was proposed for the breakdown of the Reactive Red 120 dye. The Reactive Red 120 dye structure was broken down by the cleavage of N=N azo bonds with the generation of unknown intermediate and 2‐aminobenzenesulfonic acid; it was converted into benzoquinone, which has been previously reported by Nisar et al (2017). The unknown intermediate was further reduced to sodium 4‐(6‐chloro‐4,5‐dihydro‐4‐imino‐1,3,5‐triazin‐2‐ylamino)‐5‐hydroxynaphthalene‐2,7‐disulfonate, which was reduced to 2‐(2‐amino‐2‐formylethyl)‐3‐hydroxybenzoic acid.…”
Section: Resultsmentioning
confidence: 65%
“…Selected bacterial isolates showed a variable dye color removal potential at 100 mg/l concentration of the respec- tive dyes. The variable rate of color removal with experimental azo dyes demonstrated that the rate of reduction considerably differed between dye/organism combination (Chauhan et al, 2017;Nisar et al, 2017), indicating the unique reduction potential of the bacteria as well as a different susceptibility of dyes towards reductases (Karim et al, 2018). Previously, studies (Neoh et al, 2015;Skariyachan et al, 2016;Vats and Mishra, 2017) reported that the efficiency of dye decolorization was affected by availability, survival potential, acclimatization, and efficacy of biocatalysts synthesized by microorganisms.…”
Section: Dye Decolorization Assaymentioning
confidence: 99%
“…A 25 KDa AzoR enzyme band was observed in our isolate of Serratia marcescens, after SDS PAGE analysis. Eslami et al [47] previously reported a 22 Kda AzoR from a halophilic bacterium whereas a 29 KDa AzoR was isolated by Nisar et al [48] from a Staphylococcus sp. Dong et al [49] reported many copies of NAD(P)H-dependent AzoR in Serratia sp.…”
Section: Azor Characterizationmentioning
confidence: 99%